A Performance Task Application for the Development of Elementary School Students' Perception of Hygiene and Being Healthy. (4th May 2017) - Aktepe, Vedat
ABSTRACT: In the present study, the purpose is to determine the effects of performance tasks for the topic of "hygiene and being healthy" on elementary school 4th graders' opinions about and attitudes towards the value of "hygiene and being healthy". The study employed a mixed method using both quantitative and qualitative research models. The experimental group consists of 24 and the control group consists of 23 students. The data was collected through hygiene attitude scale and being healthy attitude scale and a feelings and opinions form. In the analysis of the quantitative data, Mann-Whitney U test and in the analysis of the qualitative data descriptive analysis method were used. As a result of the quantitative analysis, it was found that there is a significant difference in hygiene value (U=66.500, p<.05), and being healthy value (U=42.000, p<.05) favoring the experimental group. As a result of the qualitative analysis, one can argue that the experimental group students displayed positive attitudes and behaviors throughout the hygiene and being healthy performance task and they will continue their hygiene and being healthy efforts after the completion of the performance task.